2011
DOI: 10.3109/0886022x.2011.623493
|View full text |Cite
|
Sign up to set email alerts
|

DD Genotype of ACE Gene in Boys: May it be a Risk Factor for Minimal Change Nephrotic Syndrome?

Abstract: It has been shown that angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism affects the circulating and cellular levels of ACE and may be a risk factor in several renal diseases. We analyzed the association of ACE gene I/D polymorphism with the clinical presentation of minimal change nephrotic syndrome (MCNS) in a Turkish child population. This study consisted of 97 children with MCNS and 144 healthy controls. Genotyping of ACE gene was performed using polymerase chain reaction (PCR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The contribution of ACE gene polymorphism to the incidence or clinical severity of INS varies among different studies [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. DD genotype or D allele were found to be associated with the overall susceptibility to INS, as well as susceptibility to MCD and FSGS in Asian children [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of ACE gene polymorphism to the incidence or clinical severity of INS varies among different studies [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. DD genotype or D allele were found to be associated with the overall susceptibility to INS, as well as susceptibility to MCD and FSGS in Asian children [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The increased Ang II plays deleterious effects on renal hemodynamics and increases the expression of some growth factors that can take part in the onset and progression of various renal diseases [3,4,5,6,7,8]. The relationship between ACE gene I/D polymorphism and INS in children has been investigated with conflicting results [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. The majority of investigations have been performed in Asian populations, with only scarce information from Europe and other parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of the recruited studies for meta-analysis was small and the result was not robust, and we stated that more genetic epidemiological investigations were required to further explore this association. Alasehirli et al 2 reported an investigation on the association of ACE I/D gene polymorphism with MCNS risk in 2011 Oct 21 (online) and found that there were no relevant differences in the allele frequencies and genotypes of ACE I/D polymorphism between patients and controls, and we hadn't included this study for our meta-analysis. They reported that the D allele and DD homozygous were not associated with MCNS risk in Turkish children.…”
mentioning
confidence: 99%
“…Interestingly, Alasehirli et al 2 first explored the association between gender and ACE gene polymorphism in the onset of MCNS and found that DD homozygous was higher in boys in children with MCNS (78.4%. vs. 50.0%), and the frequencies of DD homozygous and D allele in boys were 7.25-fold and 2.56-fold higher than II genotype and I allele in the patient group, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation